2020
DOI: 10.21203/rs.3.rs-33197/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and characterization of an immunodominant SARS-CoV-2-specific CD8 T cell response

Abstract: Global efforts are ongoing to develop vaccines against SARS-CoV-2 causing COVID-19. While there is accumulating information on antibody responses against SARS-CoV-2, less is known about CD8 T-cell recognized SARS-CoV-2 epitopes and the functional state of SARS- CoV-2-specific CD8 T cells. To address these issues, we analyzed samples from 18 COVID- 19 patients for CD8 T-cell recognition of 500 peptide HLA class I complexes, restricted by 10 common HLA alleles. Several epitopes derived from ORF1ab were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Several Shomuradova et al, 2020;Ferretti et al, 2020;Gangaev et al, 2020;Habel et al, 2020;Sahin et al, 2020;Schulien et al, 2021;Saini et al, 2020Saini et al, , 2021 performed high-resolution analysis of SARS-CoV-2-specific CD8 + T cells using HLA multimers. However, none of the studies reported similar multimer analyses for CD4 + T cells, despite the fact that, in general, HLA class II restricted SARS-CoV-2-specific T cell responses are more pronounced than HLA class I restricted T cell responses (Grifoni et al, 2020;Nelde et al, 2021).…”
Section: Assay Readoutsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several Shomuradova et al, 2020;Ferretti et al, 2020;Gangaev et al, 2020;Habel et al, 2020;Sahin et al, 2020;Schulien et al, 2021;Saini et al, 2020Saini et al, , 2021 performed high-resolution analysis of SARS-CoV-2-specific CD8 + T cells using HLA multimers. However, none of the studies reported similar multimer analyses for CD4 + T cells, despite the fact that, in general, HLA class II restricted SARS-CoV-2-specific T cell responses are more pronounced than HLA class I restricted T cell responses (Grifoni et al, 2020;Nelde et al, 2021).…”
Section: Assay Readoutsmentioning
confidence: 99%
“…Two additional HLA-A*01:01 epitopes that overlap with TTDPSFLGRY (nsp3 818-828, sequence HTTDPSFLGRY, and nsp3 819-829, sequence TTDPSFLGRYM) were also identified as particularly dominant. The study by Gangaev et al screened 50 epitopes for 10 alleles using tetramers (500 total) in 18 donors and identified nine epitopes in total, including the immunodominant nsp3 epitope restricted by HLA-A*01:01 (Gangaev et al, 2020).…”
Section: Immunodominance At the Level Of Specific Epitopes And Allelesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have begun to improve our knowledge about CD8 + T cells against SARS-CoV-2 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), but the molecular features that associate with poor clinical outcomes or differentiate them from other virus-reactive CD8 + T cells remain incompletely understood. Furthermore, despite the recent progress in understanding the biology of SARS-CoV-2-reactive and cross-reactive CD8 + T cells (5,8,9,12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), comprehensive unbiased global profiling of SARS-CoV-2reactive and cross-reactive CD8 + T cells has not been performed to date. Here, we report on data generated by single-cell RNA sequencing of virus-reactive CD8 + T cells from COVID-19 patients with different clinical severity.…”
Section: Introductionmentioning
confidence: 99%